Analyzing Modal Verbs as Politeness Markers in British and Pakistani English Communication: A Corpus Based Comparative Study - Raabia Noshair; Muhammad Usman Arshad; Yasmeen; Muhammad Ameer Hamza (`, 2025)
This research examines the use of modal verbs as indicators of politeness in British and Pakistani English conversation using a corpus-based comparative methodology. The goal was to look at how often, where, and why modal verbs are used, as well as how cultural settings affect politeness methods. The study’s backdrop is based on studies in World Englishes, politeness theory, and cross-cultural pragmatics. It shows how language reflects social and cultural values. The technique used a mixed-methods design. There were around a million words in the corpus, with 500,000 coming from British English and 500,000 from Pakistani English. The sample strategy was deliberate, choosing materials from newspapers, scholarly publications, and formal correspondence. The analytical approach was grounded on Brown and Levinson’s politeness theory, augmented with Hofstede’s cultural aspects. Quantitative study used frequency counts and chi-square statistical tests, while qualitative analysis applied concordance and collocational methods to elucidate pragmatic roles. The results showed significant disparities in how modal verbs were used: British English preferred "may" and "might" for uncertainty, whereas Pakistani English preferred "will" and "would" for assurance, respect, and unity. The results indicated that culture affects how people are polite. Pakistani English reflects collectivist and religious ideas, whereas British English emphasizes individuality and not imposing on others. Keyword: British and Pakistani, Modal verbs, Brown and Levinson’s politeness, World Englishes, Collocational, Pragmatic roles